Evaluation of the Impact of UGT Polymorphism on the Pharmacokinetics and Pharmacodynamics of the Novel PPAR Agonist Sipoglitazar. (24th January 2013) - Stringer, Frances; Ploeger, Bart A.; Jongh, Joost De; Scott, Graham; Urquhart, Richard; Karim, Aziz; Danhof, Meindert
Abstract Sipoglitazar is a peroxisome proliferator–activated receptor α, δ, and γ agonist. During phase I, a wide distribution of clearance between individuals was observed. Hypothesized to result from a polymorphism in the uridine 5′‐diphospate‐glucuronosyltransferase (UGT)2B15 enzyme, pharmacogenetic samples were collected from each individual for genotyping UGT2B15 in a subsequent phase I trial in healthy subjects (n = 524) and in 2 phase II trials in type 2 diabetes subjects (n = 627), total genotype frequency was as follows: *1/*1 (22%), *1/*2 (51%), and *2/*2 (27%). The impact of genotype on exposure was assessed using a pharmacokinetic modeling approach; the influence of genotype on efficacy was evaluated using 12‐week HbA1c change from baseline. Model analysis demonstrated UGT2B15 genotype accounted significantly for the variability in sipoglitazar clearance; however, a small fraction of subjects had a clearance that could not be explained entirely by genotype. HbA1c drop increased with daily drug dose. When stratified by both dose and genotype, HbA1c drop was larger in the UGT2B15*2/*2 compared with UGT2B15*1/*1 and UGT2B15*1/*2 genotypes (P < .05). In summary, UGT2B15 genotype is a strong predictor for sipoglitazar clearance; a greater clinical response observed in the UGT2B15*2/*2 genotype appears to confirm this. However, overlap in individual rates of clearance across genotypes remains after accounting for genotype.